LEGALITAS PROSEDURAL PRAKTIK PENYEHAT TRADISIONAL RUHANI DALAM PERSPEKTIF HUKUM ADMINISTRASI NEGARA - Abdul Madjid Podungge (Smart Education, 2026)
Abstract: This paper scrutinizes the commercial evolution of spiritual healing methodologies (Thibb al-Ruhani), as elucidated in Shaykh Muhammad Haqqi al-Nazili’s seminal text, Khazinat al-Asrar Jalilat al-Adzkar (1869). The identified research deficiency is characterized by the limited examination of public law concerning esoteric practices that have historically been segregated from contemporary administrative law frameworks. The imperative for this inquiry arises from the urgent necessity for consumer protection and legal definiteness to alleviate malpractice and religious deception through procedural instruments of state administrative law. Utilizing a normative-legal framework accompanied by statutory and conceptual methodologies, this study elucidates that internal textual rituals embody material actions (feitelijk handelen) that are obligated to adhere to the standards of Procedural Administrative Law. The licensing framework established through Traditional Healer Registration Certificates (STPT) and the Principle of Carefulness are pivotal mechanisms for preserving public order while avoiding the distortion of religious tenets. The innovative aspect encompasses a transformative reconstruction through an adaptive-hybrid